Knowledge and attitudes about HPV vaccination - Nurul Sri Rahayu; Niken Meilani; Sabar Santoso (Jurnal Kesehatan Ibu dan Anak, 2018)
HPV vaccination was one of the primary prevention efforts for cervical cancer.In 2016 of the four regencies in Yogyakarta, Kulon Progo Regency had the highest number of cervical cancer patients, which were 42 people.Especially in the Wates community health center, which contributes 8 people. SDN Gadingan and 6 Bendungan wereexperienced a decrease in DT immunization visits, which was 3.4%.While SDN 4 Bendungan had a fairly low percentage of HPV vaccination coverage compared to other SDs, which was 96.6%. This study aims to determine the level of knowledge and attitudes of respondents to HPV vaccination in 2018.This type of research was descriptive observational with cross sectional design. Research location in the Primary School of Wates Community Health Center. The subject of the research was the fifth grade female students in the State Elementary School in the Wates Community Health Center in 2018.The results showed that the mother's knowledge level was mostly enough at 66%. The results of the research on attitudes showed that most mothers had a positive attitude that was 63%. The conclusion of this study was that there was a relationship between education and work to the level of knowledge. And there was a relationship between education and maternal attitudes toward HPV vaccination, but there was no relationship between work and maternal attitudes.